Investigating the effect of amorphous carbon powder on the moisture sensitivity, fatigue performance and rutting resistance of rubberized asphalt concrete mixtures. (30th August 2019) - Ziari, Hassan; Divandari, Hassan; Hajiloo, Mojtaba; Amini, Amir
Graphical abstract: Highlights: The effects of using two waste materials (ACP and GTR) in hot mix asphalt are investigated. Laboratory performance tests and statistical analysis are presented and discussed. Amorphous carbon powder increases the moisture resistance of rubber asphalt mixtures. Asphalt mixtures containing GTR and ACP have high rutting and fatigue resistance. Abstract: In recent years, the significant importance of solid waste management, increase in the cost of bitumen and polymer modifiers have encouraged the pavement engineers to use reusable alternative sources. Ground tire rubber (GTR) and amorphous carbon powder (ACP) are considered as two industrial waste which their using in asphalt mixture prevents their releasing in the environment. This study aims to analyze moisture sensitivity, fatigue performance, and rutting resistance of asphalt mixture influenced by using GTR (8, 12, and 16% of bitumen weight) as the modifier of bitumen properties, and ACP (25, 50, and 75% of filler weight) as filler. The results of this study shows that the ACP increases the resilient modulus and indirect tensile strength of rubberized asphalt concrete (RAC) mixtures. The results revealed that despite the negative effect of GTR on the moisture resistance of asphalt mixture, ACP improves the moisture performance. The results of fracture energy also implies that using ACP decreases the fracture energy, but using the GTR improves the fatigue resistance of asphalt mixture. Furthermore, the results of dynamic creep and wheel track tests indicates that 16GTR + 50ACP has the lowest permanent deformation and highest rutting resistance. The results of ANOVA analysis demonstrates that using GTR and ACP has a considerable effect on the performance properties of asphalt mixture. Finally, the results of this study illustrate the simultaneous use cleaner production and wasted materials decreases the environmental damages in addition to improvement of physical properties of the asphalt mixture.